PENGARUH KEMUDAHAN DAN KEPERCAYAAN TERHADAP MINAT PENGGUNAAN APLIKASI DANA PADA MAHASISWA PROGRAM STUDI AKUNTANSI STIE NASIONAL BANJARMASIN - Rara Gustiana; Ruslinda Agustina (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
The aim of the study was to empirically prove the effect of convenience and trust on interest in using fund applications in students of the Banjarmasin National STIE Accounting Study Program.The method used in this study was a quantitative method by distributing questionnaires to 64 students of the Banjarmasin National STIE Accounting Study Program who were used as respondents using the SPSS Version 26.00 test tool.The conclusion is that partially and simultaneously ease and trust influence the interest in using fund applications for students of the Banjarmasin National STIE Accounting Study Program.